Thermoactivation spectroscopy of solid Ar doped with N2: Electronic Processes in Cryocrystals - Ponomaryov, A.N.; Savchenko, E.V.; Gumenchuk, G.B.; Khizhniy, I.V.; Frankowski, M.; Bondybey, V.E. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2007)
A new modification of low-temperature activation spectroscopy technique for real-time correlated study of relaxation processes in cryogenic solids was developed. This enabled us to measure simultaneously thermally stimulated exoelectron emission (TSEE) and spectrally resolved thermally stimulated luminescence (TSL) in the range from 200 to 1100 nm. This paper presents the results on TSL and TSEE from solid Ardoped with N2 exposed to irradiation by low-energy electron beam (500 eV) during deposition. The TSEEand TSL yields were measured at the heating rate of 3.2 K/min. The emissions of molecular (A3∑u+→X1 >∑g+ transition) and atomic (2D→4S transition) nitrogen in the TSL spectra and their temperature behavior were studied. Drastic changes in the intensity distribution of the molecular progression were observed with temperature rise. In low-temperature range «hot» vibrationally unrelaxed transitions were detected in contrast to «cold» vibrationally relaxed transitions observed in «high» temperature TSL. The mechanisms of the processes resulting in TSL in whole temperature range of Ar solid occurrence are suggested.